Composite antistatic auxiliary agent, preparation method and application of composite antistatic auxiliary agent in spinning polyamide filaments
By preparing composite antistatic additives, using mesoporous nano zinc oxide and graft modified allyl polyoxyethylene ether and other materials, the shortcomings of nylon filaments in antistatic, light resistance and antibacterial properties were solved, and excellent antistatic, antibacterial and anti-ultraviolet effects were achieved, and water washing resistance was improved.
Patent Information
- Application Number
- CN202411785695.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Nylon (polyamide) filaments have shortcomings in antistatic properties, light resistance and antibacterial properties. Existing antistatic agents such as polyethers have weak performance due to low polarity and ether bonds, and the problems of light resistance and antibacterial properties cannot be solved by using alone.
Mesoporous nano zinc oxide was prepared by zinc nitrate and sucrose by preparation method of composite antistatic additives, and modified by 3-glycidyl ether oxypropyltrimethoxysilane and 1-allyl-3-ethylimidazole chloride salt. Allyl polyoxyethylene ether was grafted on the supported modified nano zinc oxide to form an organic-inorganic hybrid antistatic agent, and compounded with octylphenol polyoxyethylene ether and nanocarbon black.
It achieves long-lasting, excellent anti-static, antibacterial and anti-ultraviolet effects on nylon filaments, and improves water washing resistance and enhances anti-static properties.
Smart Images

Figure CN119710954A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a composite antistatic auxiliary agent, a preparation method and application in spinning nylon filaments. Background Art
[0002] Nylon (polyamide) filament has a series of excellent properties, such as elasticity, wear resistance, corrosion resistance and other advantages, but it also has the disadvantages of poor light resistance, antistatic and antibacterial properties. In order to improve its antistatic performance, adding an antistatic agent during the preparation process is a common method, and polyether is a polymer antistatic agent widely used in various fields. For example, Chinese patent application CN103131158A discloses an antistatic masterbatch, whose formula is composed of the following weight percentages: masterbatch base material 50-72%, carbon black 9-13%, antistatic agent 8-13%, maleic anhydride grafted compatibilizer 7-15%, soap solution 9-15%, antioxidant 7-13%, the antistatic agent is fatty alcohol polyoxyethylene ether, the preparation method of the masterbatch is simple, the production cost is low, and the antistatic ability is strong. However, the antistatic performance of polyether antistatic agent is weak due to the low polarity of ether bond. Only by adding a large amount can a good antistatic effect be achieved. Moreover, when it is applied alone to nylon material, it cannot solve the problem of poor light resistance and antibacterial property of nylon material. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a composite antistatic additive, comprising the following steps:
[0004] Step (1), using zinc nitrate as a metal precursor and sucrose as a porogen to prepare mesoporous nano zinc oxide; the mesoporous nano zinc oxide is modified by 3-glycidyloxypropyltrimethoxysilane and then loaded with 1-allyl-3-ethylimidazolium chloride to obtain loaded modified nano zinc oxide;
[0005] Step (2), after allyl polyoxyethylene ether is modified with maleic anhydride, it is grafted onto the supported modified nano zinc oxide to obtain grafted modified nano zinc oxide;
[0006] Step (3), glucose and thiourea react to obtain an intermediate product A; the intermediate product A reacts with thionyl chloride and then reacts with 4-penten-1-amine to obtain an intermediate product B;
[0007] The grafted modified nano zinc oxide, the intermediate product B and the composite modified quaternary ammonium salt compound are copolymerized to obtain an organic-inorganic hybrid antistatic agent;
[0008] The organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black are mixed to obtain a composite antistatic auxiliary agent;
[0009] Wherein, the preparation method of the composite modified quaternary ammonium salt compound comprises the following steps:
[0010] Step S1, 1,3-bis(dimethylamino)-2-propanol and oxalyl chloride react to obtain an intermediate product C; the intermediate product C reacts with chloropropane to obtain a quaternary ammonium salt compound;
[0011] Step S2: After the quaternary ammonium salt compound is grafted with mercaptoethylamine, it reacts with magnolol to obtain a composite modified quaternary ammonium salt compound.
[0012] Preferably, in the step (1), the preparation method of the mesoporous nano zinc oxide is as follows: zinc nitrate hexahydrate, sucrose, ammonium chloride, ethanol, deionized water, and 25% ammonia water are mixed in a mass ratio of (8.9-17.8):(10.3-20.6):(1.6-3.2):(8-16):(10-20):(9.1-18.2), and stirred until uniform to obtain an aqueous phase; Span 80, Tween 80, and kerosene are mixed in a mass ratio of (3.5-7):(1.9-3.8):(39.5-79) The mixture was mixed and stirred until uniform to obtain an oil phase; at room temperature, the aqueous phase was added dropwise to the oil phase at a rate of 1-1.5 mL / min, and stirred to obtain a transparent oil-in-water microemulsion; the mixture was stirred at 79-81° C. and 0.01 MPa for 4.5-5.5 h, naturally cooled to room temperature, and centrifuged; the resulting precipitate was added to cyclohexane, and kept at 89-91° C. for 70-75 h to obtain a sucrose / ZnO composite material; and the sucrose / ZnO composite material was extracted with ethanol Soxhlet for 20-30 h to obtain mesoporous nano zinc oxide with an average particle size of 150 nm.
[0013] Preferably, in the step (1), the preparation method of the loaded modified nano zinc oxide is as follows: 3-glycidyloxypropyltrimethoxysilane and mesoporous nano zinc oxide are dispersed in ethanol, and then refluxed for 4-6 hours at a temperature of 75-80°C and a pH value of 4-5, centrifuged, washed, and dried to obtain surface-modified nano zinc oxide; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, mesoporous nano zinc oxide, and ethanol is (1-3):(10-15):(100-120);
[0014] Add 1-allyl-3-ethylimidazolium chloride to ethanol, ultrasonically treat for 20-40 minutes, then add surface-modified nano zinc oxide, stir at room temperature for 8-12 hours, filter, wash, and dry to obtain loaded modified nano zinc oxide; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, mesoporous nano zinc oxide, and ethanol is (5-10):(60-80):(3-5);
[0015] In the above process, zinc nitrate is used as a metal precursor and sucrose is used as a porogen, and the reverse microemulsion evaporation-induced self-assembly technology is adopted to synthesize mesoporous nano zinc oxide; then the surface of the mesoporous nano zinc oxide is modified by 3-glycidyloxypropyltrimethoxysilane, and epoxy groups are introduced on the surface of the mesoporous nano zinc oxide; then the ionic liquid 1-allyl-3-ethylimidazole chloride is loaded in the mesoporous nano zinc oxide by the impregnation method to obtain the loaded modified nano zinc oxide.
[0016] Preferably, in step (2), the preparation method of the grafted modified nano zinc oxide is:
[0017] Add allyl polyoxyethylene ether to chloroform, then add maleic anhydride and 4-dimethylaminopyridine, and react at room temperature for 60-80 hours. After the reaction is completed, evaporate the solvent to obtain modified allyl polyoxyethylene ether; wherein the mass ratio of allyl polyoxyethylene ether, chloroform, maleic anhydride, and 4-dimethylaminopyridine is (10-12):(80-100):(2.5-3):(0.05-0.1);
[0018] Add modified allyl polyoxyethylene ether and tetrabutyl ammonium bromide to deionized water, stir until uniform to obtain a mixed solution A; add the loaded modified nano zinc oxide to deionized water, ultrasonically disperse for 20-40 minutes, and then drop the mixed solution A at a rate of 1-1.5 mL / min. After the dropwise addition, heat to reflux, stir and react for 2-3 hours. After the reaction is completed, centrifuge, wash, and dry to obtain grafted modified nano zinc oxide; wherein the mass ratio of modified allyl polyoxyethylene ether, tetrabutyl ammonium bromide, and loaded modified nano zinc oxide is (8-12):(0.2-0.5):(4-6);
[0019] In the above process, maleic anhydride ring-opening reacts with the hydroxyl group of allyl polyoxyethylene ether to generate carboxyl group, thereby obtaining carboxylated modified allyl polyoxyethylene ether; the carboxyl group of the modified allyl polyoxyethylene ether reacts with the epoxy group on the surface of the loaded modified nano zinc oxide to encapsulate the loaded modified nano zinc oxide, thereby preventing the leakage of the ionic liquid during the subsequent treatment process and controlling the release rate of the ionic liquid.
[0020] Preferably, in the step (3), the preparation method of the intermediate product B is as follows: glucose, thiourea and deionized water are mixed to obtain a reaction solution, wherein the concentration of glucose in the reaction solution is 50 g / L, and the mass ratio of glucose to thiourea is 1:(0.8-1.7); the pH of the reaction solution is adjusted to 12-12.5 by using a 3 mol / L sodium hydroxide aqueous solution, reacting at 88-92° C. for 100-150 min, distilling, washing and drying to obtain the intermediate product A;
[0021] Add intermediate product A and thionyl chloride to N,N-dimethylformamide, heat to 55-65°C for reaction for 20-28h, heat to 85-92°C, add 4-pentene-1-amine, continue to react at 85-92°C for 20-28h, and rotary evaporate to obtain intermediate product B; wherein the mass ratio of intermediate product A, thionyl chloride, N,N-dimethylformamide, and 4-pentene-1-amine is (2-5):(6-10):(120-150):(3-5);
[0022] In the above process, glucose and thiourea react to form the Maillard product, namely intermediate product A; the carboxyl group in intermediate product A reacts with thionyl chloride to be converted into acyl chloride, and the acyl chloride reacts with the amino group of 4-penten-1-amine to form an amide bond, and a carbon-carbon double bond is introduced into intermediate product B.
[0023] Preferably, in the step (3), the preparation method of the organic-inorganic hybrid antistatic agent is as follows: adding the grafted modified nano zinc oxide, the intermediate product B, and the composite modified quaternary ammonium salt compound to N,N-dimethylformamide, stirring for 40-60 minutes, then adding azobisisobutyronitrile, heating to 75-80°C, continuing stirring for 5-6 hours, filtering, washing, and drying to obtain an organic-inorganic hybrid antistatic agent; wherein the mass ratio of the grafted modified nano zinc oxide, the intermediate product B, the composite modified quaternary ammonium salt compound, N,N-dimethylformamide, and azobisisobutyronitrile is (2-5):(1.5-3.5):(6-10):(120-150):(0.08-0.12);
[0024] In the above process, the intermediate product B containing carbon-carbon double bonds and the composite modified quaternary ammonium salt compound copolymerize with the double bonds in the allyl polyoxyethylene ether grafted on the surface of the nano zinc oxide to form an organic polymer cross-linked network structure on the surface of the nano zinc oxide to obtain an organic-inorganic hybrid antistatic agent;
[0025] Preferably, in step (3), the mass ratio of the organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black is (4-6):(2-4):(1-2).
[0026] Furthermore, in step (3), the method for preparing the composite modified quaternary ammonium salt compound comprises the following steps:
[0027] Step S1, adding 1,3-bis(dimethylamino)-2-propanol to N,N-dimethylformamide, adding dropwise a 9.5% oxalyl chloride / N,N-dimethylformamide mixture at a rate of 0.8-1.2 mL / min under stirring in an ice-water bath, stirring for 1.5-2.5 h, and then continuing the reaction at room temperature for 3.5-4.5 h. After the reaction is completed, rotary evaporation is performed to obtain an intermediate product C; wherein the mass ratio of 1,3-bis(dimethylamino)-2-propanol, N,N-dimethylformamide, and oxalyl chloride / N,N-dimethylformamide mixture is (1.5-3):(50-80):(20-35);
[0028] Under stirring conditions, the intermediate product C and acetone are mixed, and then chloropropane is added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the mixture is stirred and reacted at 38-42° C. for 20-28 hours. After the reaction is completed, the mixture is evaporated to obtain a quaternary ammonium salt compound; wherein the mass ratio of the intermediate product C, acetone, and chloropropane is (2.4-3.6):(50-80):(1.8-4.2);
[0029] In the above process, the hydroxyl group in 1,3-di(dimethylamino)-2-propanol undergoes an esterification reaction with the acyl chloride at one end of oxalyl chloride to obtain an intermediate product C; the intermediate product C is combined with chloropropane through a quaternization reaction to form a quaternary ammonium salt compound containing two quaternary ammonium salt groups;
[0030] Step S2, adding a quaternary ammonium salt compound to tetrahydrofuran, stirring for 20-40 minutes, and dripping a 6.3% mass fraction of mercaptoethylamine / methanol mixed solution at a rate of 1-2 mL / min in a nitrogen atmosphere. After the dripping, stirring and reacting at room temperature for 10-14 hours, evaporating, and obtaining a grafted modified quaternary ammonium salt compound; wherein the mass ratio of the quaternary ammonium salt compound, tetrahydrofuran, and mercaptoethylamine / methanol mixed solution is (3.2-6.4):(30-50):(12.7-21.1);
[0031] Add magnolol to ethanol, ultrasonically treat for 20-40 minutes, heat to 60-70°C, then add grafted modified quaternary ammonium salt compound and 0.5% azobisisobutyronitrile / ethanol solution, stir and react for 3-5 hours, filter, wash and dry after the reaction to obtain a composite modified quaternary ammonium salt compound, wherein the mass ratio of magnolol, ethanol, grafted modified quaternary ammonium salt compound and azobisisobutyronitrile / ethanol solution is (2.7-5.4):(50-80):(3.6-7.2):(15-20). The composite antistatic additive prepared by the preparation method of the composite antistatic additive;
[0032] In the above process, the acyl chloride in the quaternary ammonium salt compound reacts with the amino group of mercaptoethylamine to form an amide bond to obtain a grafted modified quaternary ammonium salt compound containing a thiol group, and the thiol group is then combined with the carbon-carbon double bond at one end of magnolol through a thiol-ene click reaction to obtain a composite modified quaternary ammonium salt compound.
[0033] The composite antistatic auxiliary agent is used in spinning nylon filaments.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The organic-inorganic hybrid antistatic agent of the present invention is obtained by copolymerization of graft-modified nano zinc oxide, intermediate product B, and composite modified quaternary ammonium salt compound, wherein:
[0036] (1) Graft-modified nano zinc oxide is obtained by grafting modified allyl polyoxyethylene ether on the surface of mesoporous nano zinc oxide loaded with ionic liquid 1-allyl-3-ethylimidazolium chloride. Nano zinc oxide has excellent conductivity, antibacterial property, ultraviolet absorption and non-toxicity. Allyl polyoxyethylene ether and ionic liquid also have excellent antistatic properties. Encapsulating the ionic liquid in the mesoporous nano zinc oxide can achieve the sustained release of the ionic liquid. Moreover, the imidazolium cation in the ionic liquid forms a hydrogen bond with the C=O of the amide group in the polyamide structure of the nylon filament, and the chloride anion interacts with the NH of the amide group, thereby exerting a long-lasting and excellent antistatic property. Therefore, the graft-modified nano zinc oxide of the present invention has a long-lasting antistatic, antibacterial and anti-ultraviolet effect.
[0037] (2) Intermediate product B is obtained by the reaction of the Maillard product (intermediate product A) with 4-pentene-1-amine. The π bonds (CN and CS) in intermediate product A have good ultraviolet absorption properties and can form NH + The electron-rich sulfur element is easy to bind to the cell wall and exhibits a bactericidal effect by reducing bacterial activity. Therefore, the intermediate product A of the present invention has anti-ultraviolet and antibacterial properties. More importantly, the intermediate product A has high adhesion and can firmly adhere to the nylon filaments, and the aldehyde group therein can also form a covalent bond with the nylon filaments containing amino groups (such as PA6, etc.), thereby improving the wash resistance.
[0038] (3) The composite modified quaternary ammonium salt compound contains two quaternary ammonium salt groups and an anti-ultraviolet magnolol structure, so it has antistatic, antibacterial and anti-ultraviolet effects. It also contains an amide group, which can form hydrogen bonds with C=O and NH in the polyamide structure in nylon, thereby improving the compatibility between the organic-inorganic hybrid antistatic agent and nylon filaments.
[0039] In summary, organic-inorganic hybrid antistatic agents work together in many aspects and have excellent antistatic, antibacterial and anti-ultraviolet effects. When used in spinning nylon filaments, they have good water wash resistance. When used in combination with octylphenol polyoxyethylene ether and nano-carbon black, they can exert better antistatic effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a process flow chart of the preparation method of the composite antistatic auxiliary agent of the present invention;
[0041] Figure 2 It is a schematic diagram of the synthesis of the intermediate product A of the present invention;
[0042] Figure 3 It is a schematic diagram of the synthesis of the quaternary ammonium salt compound of the present invention;
[0043] Figure 4 It is a schematic diagram of the synthesis of the composite modified quaternary ammonium salt compound of the present invention;
[0044] Figure 5 It is a comparison chart of the surface resistivity test of the samples obtained by using the composite antistatic agent prepared in Examples 2-4 of the present invention and Comparative Examples 1-5 in nylon filaments;
[0045] Figure 6 It is a UPF test comparison chart of samples obtained by using the composite antistatic agent prepared in Examples 2-4 of the present invention and Comparative Examples 1-5 in nylon filaments. DETAILED DESCRIPTION
[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1
[0048] This embodiment discloses a method for preparing a composite modified quaternary ammonium salt compound, comprising the following steps:
[0049] Step S1, adding 2.3 g of 1,3-bis(dimethylamino)-2-propanol to 65 g of N,N-dimethylformamide, and dripping 27.5 g of a 9.5% by mass oxalyl chloride / N,N-dimethylformamide mixed solution at a rate of 1 mL / min in an ice-water bath under stirring, stirring for 2 h, and then continuing to react at room temperature for 4 h. After the reaction is completed, the solvent and excess oxalyl chloride are removed by rotary evaporation at 80° C. to obtain an intermediate product C;
[0050] Under stirring conditions, 3 g of intermediate product C and 65 g of acetone were mixed, and then 3 g of chloropropane was added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was stirred and reacted at 40° C. for 24 h. After the reaction was completed, the solvent and excess chloropropane were evaporated to obtain a quaternary ammonium salt compound;
[0051] Step S2, adding 4.8 g of a quaternary ammonium salt compound to 40 g of tetrahydrofuran, stirring for 30 min, and in a nitrogen atmosphere, dropping 16.9 g of a 6.3% by mass thioethylamine / methanol mixture at a rate of 1.5 mL / min, stirring at room temperature for 12 h, and evaporating the solvent to obtain a grafted modified quaternary ammonium salt compound;
[0052] 4.1 g of magnolol was added to 65 g of ethanol, and the mixture was ultrasonically treated for 30 min, and then heated to 65° C., and then 5.4 g of the grafted modified quaternary ammonium salt compound and 17.5 g of a 0.5% azobisisobutyronitrile / ethanol solution were added, and the mixture was stirred for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite modified quaternary ammonium salt compound.
[0053] Example 2
[0054] This embodiment discloses a method for preparing a composite antistatic additive, comprising the following steps:
[0055] Step (1), 8.9g zinc nitrate hexahydrate, 10.3g sucrose, 1.6g ammonium chloride, 8g ethanol, 10g deionized water, 9.1g ammonia water with a mass fraction of 25%, and stirring until uniform to obtain an aqueous phase; 3.5g Span 80, 1.9g Tween 80, and 39.5g kerosene are mixed and stirred until uniform to obtain an oil phase; at room temperature, the aqueous phase is added dropwise to the oil phase at a rate of 1mL / min, and stirred to obtain a transparent water-in-oil microemulsion, and then stirred at 79°C and 0.01MPa for 5.5h, naturally cooled to room temperature, centrifuged, and the obtained precipitate is added to cyclohexane, and maintained at 89°C for 75h to obtain a sucrose / ZnO composite material, and the sucrose / ZnO composite material is extracted with ethanol Soxhlet for 20h to obtain a mesoporous nano zinc oxide with an average particle size of 150nm;
[0056] Dispersing 1 g of 3-glycidyloxypropyltrimethoxysilane and 10 g of mesoporous nano zinc oxide in 100 g of ethanol, and then refluxing for 6 h at a temperature of 75° C. and a pH value of 4, centrifuging, washing, and drying to obtain surface-modified nano zinc oxide;
[0057] 5 g of 1-allyl-3-ethylimidazolium chloride was added to 60 g of ethanol, and after ultrasonic treatment for 20 min, 3 g of surface-modified nano zinc oxide was added, and the mixture was stirred at room temperature for 8 h, filtered, washed, and dried to obtain loaded modified nano zinc oxide;
[0058] Step (2), adding 10 g of allyl polyoxyethylene ether to 80 g of chloroform, and then adding 2.5 g of maleic anhydride and 0.05 g of 4-dimethylaminopyridine, reacting at room temperature for 60 hours, and after the reaction is completed, evaporating the solvent to obtain modified allyl polyoxyethylene ether;
[0059] 8 g of modified allyl polyoxyethylene ether and 0.2 g of tetrabutylammonium bromide were added to 30 g of deionized water, and stirred until uniform to obtain a mixed solution A; 4 g of loaded modified nano zinc oxide was added to 100 g of deionized water, and ultrasonically dispersed for 20 min, and then the mixed solution A was added dropwise at a rate of 1 mL / min. After the addition, the temperature was raised to reflux, and the mixture was stirred for reaction for 2 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain grafted modified nano zinc oxide;
[0060] Step (3), mixing glucose, thiourea and deionized water to obtain a reaction solution, wherein the concentration of glucose in the reaction solution is 50 g / L, and the mass ratio of glucose to thiourea is 1:0.8; adjusting the pH of the reaction solution to 12 with a 3 mol / L sodium hydroxide aqueous solution, reacting at 88° C. for 150 min, distilling, washing the crude product with ethanol, and vacuum drying at 50° C. to obtain an intermediate product A;
[0061] 2 g of intermediate product A and 6 g of thionyl chloride were added to 120 g of N,N-dimethylformamide, heated to 55°C for reaction for 28 h, then heated to 85°C to remove excess thionyl chloride, and then 3 g of 4-pentene-1-amine was added, and the reaction was continued at 85°C for 28 h, and the solvent and excess 4-pentene-1-amine were removed by rotary evaporation to obtain intermediate product B;
[0062] 2g of grafted modified nano zinc oxide, 1.5g of intermediate product B, and 6g of composite modified quaternary ammonium salt compound were added to 120g of N,N-dimethylformamide, stirred for 40min, and then 0.08g of azobisisobutyronitrile was added, the temperature was raised to 75°C, and stirring was continued for 6h, filtered, washed, and dried to obtain an organic-inorganic hybrid antistatic agent;
[0063] The organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black are mixed in a mass ratio of 4:2:1 to obtain a composite antistatic auxiliary agent.
[0064] Example 3
[0065] This embodiment discloses a method for preparing a composite antistatic additive, comprising the following steps:
[0066] Step (1), 17.8g zinc nitrate hexahydrate, 20.6g sucrose, 3.2g ammonium chloride, 16g ethanol, 20g deionized water, and 18.2g ammonia water with a mass fraction of 25% are mixed and stirred to obtain a water phase; 7g Span 80, 3.8g Tween 80, and 79g kerosene are mixed and stirred to obtain an oil phase; at room temperature, the water phase is added dropwise to the oil phase at a rate of 1.5mL / min, and stirred to obtain a transparent water-in-oil microemulsion, and then stirred at 81°C and 0.01MPa for 5.5h, naturally cooled to room temperature, centrifuged, and the obtained precipitate is added to cyclohexane, and kept at 91°C for 70h to obtain a sucrose / ZnO composite material, and the sucrose / ZnO composite material is extracted with ethanol Soxhlet for 30h to obtain a mesoporous nano zinc oxide with an average particle size of 150nm;
[0067] Disperse 3 g of 3-glycidyloxypropyltrimethoxysilane and 15 g of mesoporous nano zinc oxide in 120 g of ethanol, and then reflux for 4 h at 80° C. and pH 5, centrifuge, wash, and dry to obtain surface-modified nano zinc oxide;
[0068] 10 g of 1-allyl-3-ethylimidazolium chloride was added to 80 g of ethanol, and after ultrasonic treatment for 40 min, 5 g of surface-modified nano zinc oxide was added, and the mixture was stirred at room temperature for 12 h, filtered, washed, and dried to obtain the loaded modified nano zinc oxide;
[0069] Step (2), adding 12 g of allyl polyoxyethylene ether to 100 g of chloroform, and then adding 3 g of maleic anhydride and 0.1 g of 4-dimethylaminopyridine, reacting at room temperature for 60 h. After the reaction is completed, evaporating the solvent to obtain modified allyl polyoxyethylene ether;
[0070] 12g of modified allyl polyoxyethylene ether and 0.5g of tetrabutylammonium bromide were added to 40g of deionized water, and stirred until uniform to obtain a mixed solution A; 6g of loaded modified nano zinc oxide was added to 120g of deionized water, and ultrasonically dispersed for 40min, and then the mixed solution A was added dropwise at a rate of 1.5mL / min. After the addition, the temperature was raised to reflux, and the reaction was stirred for 3h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain grafted modified nano zinc oxide;
[0071] Step (3), mixing glucose, thiourea and deionized water to obtain a reaction solution, wherein the concentration of glucose in the reaction solution is 50 g / L, and the mass ratio of glucose to thiourea is 1:1.7; adjusting the pH of the reaction solution to 12.5 with a 3 mol / L sodium hydroxide aqueous solution, reacting at 92° C. for 100 min, distilling, washing the crude product with ethanol, and vacuum drying at 60° C. to obtain an intermediate product A;
[0072] 5 g of intermediate product A and 10 g of thionyl chloride were added to 150 g of N,N-dimethylformamide, heated to 65°C for reaction for 20 h, then heated to 92°C to remove excess thionyl chloride, and then 5 g of 4-pentene-1-amine was added, and the reaction was continued at 92°C for 20 h, and the solvent and excess 4-pentene-1-amine were removed by rotary evaporation to obtain intermediate product B;
[0073] 5 g of grafted modified nano zinc oxide, 3.5 g of intermediate product B, and 10 g of composite modified quaternary ammonium salt compound were added to 150 g of N,N-dimethylformamide, stirred for 60 min, and then 0.12 g of azobisisobutyronitrile was added, the temperature was raised to 80° C., and stirring was continued for 5 h, filtered, washed, and dried to obtain an organic-inorganic hybrid antistatic agent;
[0074] The organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black are mixed in a mass ratio of 6:4:2 to obtain a composite antistatic auxiliary agent.
[0075] Example 4
[0076] This embodiment discloses a method for preparing a composite antistatic additive, comprising the following steps:
[0077] Step (1), 13.4g zinc nitrate hexahydrate, 15.5g sucrose, 2.4g ammonium chloride, 12g ethanol, 15g deionized water, and 13.7g ammonia water with a mass fraction of 25% are mixed and stirred to obtain a water phase; 5.3g Span 80, 2.9g Tween 80, and 59.3g kerosene are mixed and stirred to obtain an oil phase; at room temperature, the water phase is added dropwise to the oil phase at a rate of 1.2mL / min, and stirred to obtain a transparent water-in-oil microemulsion, and then stirred at 80°C and 0.01MPa for 5h, cooled naturally to room temperature, centrifuged, and the obtained precipitate is added to cyclohexane, and kept at 89-91°C for 72h to obtain a sucrose / ZnO composite material, and the sucrose / ZnO composite material is extracted with ethanol Soxhlet for 25h to obtain a mesoporous nano zinc oxide with an average particle size of 150nm;
[0078] Disperse 2 g of 3-glycidyloxypropyltrimethoxysilane and 12.5 g of mesoporous nano zinc oxide in 110 g of ethanol, and then reflux for 5 h at 78° C. and pH 4.5, centrifuge, wash, and dry to obtain surface-modified nano zinc oxide;
[0079] 7.5 g of 1-allyl-3-ethylimidazolium chloride was added to 70 g of ethanol, and after ultrasonic treatment for 30 min, 4 g of surface-modified nano zinc oxide was added, and the mixture was stirred at room temperature for 8-12 h, filtered, washed, and dried to obtain the loaded modified nano zinc oxide;
[0080] Step (2), adding 11 g of allyl polyoxyethylene ether to 90 g of chloroform, and then adding 2.8 g of maleic anhydride and 0.08 g of 4-dimethylaminopyridine, reacting at room temperature for 70 h. After the reaction is completed, evaporating the solvent to obtain modified allyl polyoxyethylene ether;
[0081] 10g of modified allyl polyoxyethylene ether and 0.3g of tetrabutylammonium bromide were added to 35g of deionized water, and stirred until uniform to obtain a mixed solution A; 5g of loaded modified nano zinc oxide was added to 110g of deionized water, and ultrasonically dispersed for 30min, and then the mixed solution A was added dropwise at a rate of 1.2mL / min. After the addition, the temperature was raised to reflux, and the reaction was stirred for 2.5h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain grafted modified nano zinc oxide;
[0082] Step (3), mixing glucose, thiourea and deionized water to obtain a reaction solution, wherein the concentration of glucose in the reaction solution is 50 g / L, and the mass ratio of glucose to thiourea is 1:1.3; adjusting the pH of the reaction solution to 12.3 with a 3 mol / L sodium hydroxide aqueous solution, reacting at 90° C. for 120 min, distilling, washing the crude product with ethanol, and vacuum drying at 55° C. to obtain an intermediate product A;
[0083] 3.5 g of intermediate product A and 8 g of thionyl chloride were added to 135 g of N,N-dimethylformamide, heated to 60°C for reaction for 24 h, then heated to 89°C to remove excess thionyl chloride, and then 4 g of 4-pentene-1-amine was added, and the reaction was continued at 89°C for 24 h, and the solvent and excess 4-pentene-1-amine were removed by rotary evaporation to obtain intermediate product B;
[0084] 3.5 g of grafted modified nano zinc oxide, 2.5 g of intermediate product B, and 8 g of composite modified quaternary ammonium salt compound were added to 135 g of N,N-dimethylformamide, stirred for 50 min, and then 0.1 g of azobisisobutyronitrile was added, the temperature was raised to 78° C., and stirring was continued for 5.5 h, filtered, washed, and dried to obtain an organic-inorganic hybrid antistatic agent;
[0085] The organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black are mixed in a mass ratio of 5:3:1.5 to obtain a composite antistatic auxiliary agent.
[0086] The composite modified quaternary ammonium salt compound used in the above Examples 2-4 is the composite modified quaternary ammonium salt compound prepared in Example 1.
[0087] Comparative Example 1
[0088] Compared with Example 4, in the process of preparing grafted modified nano zinc oxide in Comparative Example 1, surface modified nano zinc oxide was used instead of modified loaded modified nano zinc oxide, and other conditions remained unchanged.
[0089] Comparative Example 2
[0090] Compared with Example 4, in the process of preparing the organic-inorganic hybrid antistatic agent in Comparative Example 2, modified allyl polyoxyethylene ether was used instead of grafted modified nano zinc oxide, and other conditions remained unchanged.
[0091] Comparative Example 3
[0092] Compared with Example 4, in the process of preparing the organic-inorganic hybrid antistatic agent in Comparative Example 3, no grafted modified nano zinc oxide was added, and other conditions remained unchanged.
[0093] Comparative Example 4
[0094] Compared with Example 4, in the process of preparing the organic-inorganic hybrid antistatic agent in Comparative Example 4, the intermediate product B was not added, and other conditions remained unchanged.
[0095] Comparative Example 5
[0096] Compared with Example 4, in the process of preparing the organic-inorganic hybrid antistatic agent in Comparative Example 5, no composite modified quaternary ammonium salt compound was added, and other conditions remained unchanged.
[0097] In the above embodiments and comparative examples, sucrose, with a particle size of 200 mesh and a purity of 99%, is from Langfang Huinuo Fine Chemical Co., Ltd.; Span 80, with an appearance of yellow oily liquid and an HLB value of 4.3, is from Shandong Haochen New Material Technology Co., Ltd.; Tween 80, with an appearance of amber viscous oil, a specific gravity of 1.06-1.09, and an HLB value of 15, is from Taizhou Jiayin Chemical Co., Ltd.; kerosene, with a density of 0.79 (g / mL) and an effective ingredient content of 99.98%, is from Handan Qianxiong Oil Technology Co., Ltd.; allyl polyoxyethylene ether, with an effective ingredient content of 99%, model APEG-400, a molecular weight of 400, and a hydroxyl value (mg KOH / g) of 127-155, is from Jiangsu Hai'an Petrochemical Plant; octylphenol polyoxyethylene ether, with an effective substance content of 99%, model NP-40, and an appearance of white flakes, is from Tianjin Daixu Chemical Trading Co., Ltd.; nano carbon black, with an average particle size of 25 nm, is from Tianjin Baochi Chemical Technology Co., Ltd.
[0098] Experimental example
[0099] The composite antistatic additives prepared in Examples 2-4 of the present invention and Comparative Examples 1-5 were respectively mixed with PA6 chips at a mass ratio of 3:100, melt-extruded and metered and homogenized through a screw extruder into a spinning box, and then metered and extruded by a metering pump, cooled and solidified by side blowing, oiled and bundled, pre-networked, first-level stretching by a cold roller, second-level stretching and heat setting by a hot roller, a sub-network device, and wound to form nylon filament samples, which were respectively recorded as Sample 2, Sample 3, Sample 4 and Comparative Sample 1, Comparative Sample 2, Comparative Sample 3, Comparative Sample 4, and Comparative Sample 5.
[0100] Perform performance tests on each group of samples.
[0101] 1. Antistatic performance test: Test in accordance with GB / T 1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials".
[0102] 2. Antibacterial performance test: Escherichia coli and Staphylococcus aureus were used as test bacteria. The test steps were based on GB / T20944.3-2008. First, the concentration of live bacteria in the flask at "0" contact time was tested, recorded as W0, and then the number of colonies was tested when the oscillation contact time was 18h, recorded as Wt. The results are shown in Table 1. The calculation formula for the antibacterial rate Y is as follows: Y = (W t -W0) / W0×100%. Then, the antibacterial rate of each group of samples after washing 50 times was tested in the same way.
[0103] 3. Anti-ultraviolet performance test: The anti-ultraviolet performance is characterized by the average value of the anti-ultraviolet factor (UPF). Referring to the standard GB / T18830-2009, a small hosiery machine is first used to make garters for each group of samples, and then the garters are placed on the sample platform of the ultraviolet transmittance tester. 10 points are evenly selected for testing. The test ultraviolet wavelength is 250-450nm, and the transmittance is 0-100%. Then the UPF is calculated according to the following formula.
[0104]
[0105] Where: T λ is the spectral transmittance of the sample at wavelength λ, S λ is the relative erythema dose spectral effect, E λ is the solar spectrum radiance, △λ is the wavelength interval.
[0106] The test results are shown in Table 1:
[0107] Table 1
[0108]
[0109]
[0110] From the test results in Table 1, it can be seen that samples 2-4 of the present invention have excellent antistatic, antibacterial, anti-ultraviolet effects and water-washing resistance. From the comparison of comparative samples 1-3 and sample 4, it can be seen that ionic liquids, nano zinc oxide, and allyl polyoxyethylene ether all have different degrees of influence on the antistatic effect of organic-inorganic hybrid antistatic agents. Due to the presence of nano zinc oxide, the grafted modified nano zinc oxide is endowed with anti-ultraviolet and antibacterial properties, thereby affecting the anti-ultraviolet and antibacterial properties of each group of samples; from the comparison of comparative sample 4 and sample 4, it can be seen that the intermediate product B has good ultraviolet absorption performance due to the presence of π bonds (CN and CS), and can form NH under acidic conditions. + The electron-rich sulfur element is easy to bind to the cell wall and exhibits a bactericidal effect by reducing the activity of bacteria, thereby affecting the anti-ultraviolet and antibacterial properties of each group of samples. The intermediate product A has a significant effect on the water washability of the nylon filament sample due to its adhesion and the formation of covalent bonds with the nylon filament. From the comparison between the comparative sample 5 and the sample 4, it can be seen that the composite modified quaternary ammonium salt compound contains two quaternary ammonium salt groups and an anti-ultraviolet magnolol structure, so it has antistatic, antibacterial and anti-ultraviolet effects, and it also contains an amide group. The amide group can form hydrogen bonds with C=O and NH in the polyamide structure in the nylon, thereby improving the compatibility between the organic-inorganic hybrid antistatic agent and the nylon filament, so that the organic-inorganic hybrid antistatic agent can exert a better effect.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite antistatic additive, characterized in that: The following steps are involved: Step (1), using zinc nitrate as a metal precursor and sucrose as a porogen to prepare mesoporous nano zinc oxide; the mesoporous nano zinc oxide is modified by 3-glycidyloxypropyltrimethoxysilane and then loaded with 1-allyl-3-ethylimidazolium chloride to obtain loaded modified nano zinc oxide; Step (2), after allyl polyoxyethylene ether is modified with maleic anhydride, it is grafted onto the supported modified nano zinc oxide to obtain grafted modified nano zinc oxide; Step (3), glucose and thiourea react to obtain an intermediate product A; the intermediate product A reacts with thionyl chloride and then reacts with 4-penten-1-amine to obtain an intermediate product B; The grafted modified nano zinc oxide, the intermediate product B and the composite modified quaternary ammonium salt compound are copolymerized to obtain an organic-inorganic hybrid antistatic agent; The organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether and nano carbon black are mixed to obtain a composite antistatic auxiliary agent; Wherein, the preparation method of the composite modified quaternary ammonium salt compound comprises the following steps: Step S1, 1,3-bis(dimethylamino)-2-propanol and oxalyl chloride react to obtain an intermediate product C; the intermediate product C reacts with chloropropane to obtain a quaternary ammonium salt compound; Step S2: After the quaternary ammonium salt compound is grafted with mercaptoethylamine, it reacts with magnolol to obtain a composite modified quaternary ammonium salt compound.
2. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (1), the preparation method of the mesoporous nano zinc oxide is as follows: zinc nitrate hexahydrate, sucrose, ammonium chloride, ethanol, deionized water, and 25% ammonia water are mixed in a mass ratio of (8.9-17.8):(10.3-20.6):(1.6-3.2):(8-16):(10-20):(9.1-18.2), and stirred until uniform to obtain an aqueous phase; Span 80, Tween 80, and kerosene are mixed in a mass ratio of (3.5-7):(1.9-3.8):(39.5-79), The method comprises the steps of stirring until uniform to obtain an oil phase; at room temperature, dropping the aqueous phase into the oil phase at a rate of 1-1.5 mL / min, stirring to obtain a transparent water-in-oil microemulsion, stirring at 79-81° C. and 0.01 MPa for 4.5-5.5 hours, naturally cooling to room temperature, centrifuging, adding the obtained precipitate into cyclohexane, and maintaining the mixture at 89-91° C. for 70-75 hours to obtain a sucrose / ZnO composite material; and extracting the sucrose / ZnO composite material with ethanol Soxhlet for 20-30 hours to obtain a mesoporous nano zinc oxide with an average particle size of 150 nm.
3. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (1), the preparation method of the loaded modified nano zinc oxide is as follows: 3-glycidyloxypropyltrimethoxysilane and mesoporous nano zinc oxide are dispersed in ethanol, and then refluxed for 4-6 hours at a temperature of 75-80°C and a pH value of 4-5, centrifuged, washed, and dried to obtain surface-modified nano zinc oxide; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, mesoporous nano zinc oxide, and ethanol is (1-3):(10-15):(100-120); 1-allyl-3-ethylimidazole chloride is added to ethanol, and after ultrasonic treatment for 20-40 minutes, surface-modified nano zinc oxide is added, and the mixture is stirred at room temperature for 8-12 hours, filtered, washed, and dried to obtain loaded modified nano zinc oxide; wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, mesoporous nano zinc oxide, and ethanol is (5-10):(60-80):(3-5).
4. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (2), the preparation method of the grafted modified nano zinc oxide is: Add allyl polyoxyethylene ether to chloroform, then add maleic anhydride and 4-dimethylaminopyridine, and react at room temperature for 60-80 hours. After the reaction is completed, evaporate the solvent to obtain modified allyl polyoxyethylene ether; wherein the mass ratio of allyl polyoxyethylene ether, chloroform, maleic anhydride, and 4-dimethylaminopyridine is (10-12):(80-100):(2.5-3):(0.05-0.1); Add modified allyl polyoxyethylene ether and tetrabutyl ammonium bromide to deionized water and stir until uniform to obtain a mixed solution A; add the loaded modified nano zinc oxide to deionized water, ultrasonically disperse for 20-40 minutes, and then drop the mixed solution A at a rate of 1-1.5 mL / min. After the dropwise addition, heat to reflux and stir to react for 2-3 hours. After the reaction is completed, centrifuge, wash, and dry to obtain grafted modified nano zinc oxide; wherein the mass ratio of modified allyl polyoxyethylene ether, tetrabutyl ammonium bromide, and loaded modified nano zinc oxide is (8-12):(0.2-0.5):(4-6).
5. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (3), the preparation method of the intermediate product B is as follows: glucose, thiourea and deionized water are mixed to obtain a reaction solution, wherein the concentration of glucose in the reaction solution is 50 g / L, and the mass ratio of glucose to thiourea is 1:(0.8-1.7); the pH of the reaction solution is adjusted to 12-12.5 by using a 3 mol / L sodium hydroxide aqueous solution, reacting at 88-92° C. for 100-150 min, distilling, washing and drying to obtain an intermediate product A; Add intermediate product A and thionyl chloride to N,N-dimethylformamide, heat to 55-65°C for reaction for 20-28h, raise the temperature to 85-92°C, add 4-pentene-1-amine, continue to react at 85-92°C for 20-28h, and rotary evaporate to obtain intermediate product B; wherein the mass ratio of intermediate product A, thionyl chloride, N,N-dimethylformamide and 4-pentene-1-amine is (2-5):(6-10):(120-150):(3-5).
6. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (3), the preparation method of the organic-inorganic hybrid antistatic agent is as follows: adding grafted modified nano zinc oxide, intermediate product B, and composite modified quaternary ammonium salt compound to N,N-dimethylformamide, stirring for 40-60 minutes, then adding azobisisobutyronitrile, heating to 75-80°C, continuing stirring for 5-6 hours, filtering, washing, and drying to obtain an organic-inorganic hybrid antistatic agent; wherein the mass ratio of grafted modified nano zinc oxide, intermediate product B, composite modified quaternary ammonium salt compound, N,N-dimethylformamide, and azobisisobutyronitrile is (2-5):(1.5-3.5):(6-10):(120-150):(0.08-0.12).
7. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (3), the mass ratio of the organic-inorganic hybrid antistatic agent, octylphenol polyoxyethylene ether, and nano carbon black is (4-6):(2-4):(1-2).
8. The method for preparing the composite antistatic auxiliary agent according to claim 1, characterized in that: In the step (3), the method for preparing the composite modified quaternary ammonium salt compound comprises the following steps: Step S1, adding 1,3-bis(dimethylamino)-2-propanol to N,N-dimethylformamide, adding dropwise a 9.5% oxalyl chloride / N,N-dimethylformamide mixture at a rate of 0.8-1.2 mL / min under stirring in an ice-water bath, stirring for 1.5-2.5 h, and then continuing the reaction at room temperature for 3.5-4.5 h. After the reaction is completed, rotary evaporation is performed to obtain an intermediate product C; wherein the mass ratio of 1,3-bis(dimethylamino)-2-propanol, N,N-dimethylformamide, and oxalyl chloride / N,N-dimethylformamide mixture is (1.5-3):(50-80):(20-35); Under stirring conditions, the intermediate product C and acetone are mixed, and then chloropropane is added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the mixture is stirred and reacted at 38-42° C. for 20-28 hours. After the reaction is completed, the mixture is evaporated to obtain a quaternary ammonium salt compound; wherein the mass ratio of the intermediate product C, acetone, and chloropropane is (2.4-3.6):(50-80):(1.8-4.2); Step S2, adding a quaternary ammonium salt compound to tetrahydrofuran, stirring for 20-40 minutes, and dripping a 6.3% mass fraction of mercaptoethylamine / methanol mixed solution at a rate of 1-2 mL / min in a nitrogen atmosphere. After the dripping, stirring and reacting at room temperature for 10-14 hours, evaporating, and obtaining a grafted modified quaternary ammonium salt compound; wherein the mass ratio of the quaternary ammonium salt compound, tetrahydrofuran, and mercaptoethylamine / methanol mixed solution is (3.2-6.4):(30-50):(12.7-21.1); Add magnolol to ethanol, perform ultrasonic treatment for 20-40 minutes, heat to 60-70°C, add grafted modified quaternary ammonium salt compound and 0.5% azobisisobutyronitrile / ethanol solution, stir and react for 3-5 hours. After the reaction, filter, wash and dry to obtain a composite modified quaternary ammonium salt compound, wherein the mass ratio of magnolol, ethanol, grafted modified quaternary ammonium salt compound and azobisisobutyronitrile / ethanol solution is (2.7-5.4):(50-80):(3.6-7.2):(15-20).
9. A composite antistatic auxiliary agent prepared by the method for preparing a composite antistatic auxiliary agent according to any one of claims 1 to 8.
10. Use of the composite antistatic additive according to claim 9 in spinning nylon filaments.
Citation Information
Patent Citations
Anti-static electricity color master batch and preparation method thereof
CN103131158A
Antistatic woven belt
CN111441122A
Preparation method and application of mesoporous carbon sphere modified Co-CoP composite electrocatalyst
CN112921353A
PH responsive intelligent controlled-release antibacterial degradable packaging film and preparation method and application thereof
CN113601933A
Urban sewage treatment agent as well as preparation method and application thereof
CN113788549A